The heterogeneous effect of oil discoveries on democracy. (1st May 2019) - Masi, Tania; Ricciuti, Roberto
Abstract: This paper evaluates the existence of a resource curse on political regimes using the Synthetic Control Method. Focusing on 12 countries, we compare their democracy level with the weighted democracy level of countries that have not experienced oil shocks and have similar pre‐event characteristics. We find that the exogenous variation in oil endowment does not have the same effect on all countries. In most cases, the event has a negative effect in the long run, but countries with a pre‐existing high level of democracy are not negatively affected.